2021
DOI: 10.20944/preprints202101.0125.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature’s Role in Supporting Health During the COVID-19 Pandemic: A Geospatial and Socioecological Study

Abstract: The COVID-19 pandemic has brought about unprecedented changes to human lifestyles across the world. The virus and associated social restriction measures have been linked to an increase in mental health conditions. A considerable body of evidence shows that spending time in and engaging with nature can improve human health and wellbeing. Our study explores nature’s role in supporting health during the COVID-19 pandemic. We created web-based questionnaires with validated health instruments and conducte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Some countries did not impose strict restrictions, especially during the early time of the pandemic. For instance, a study conducted by Robinson et al (2021) found that people's greenspace use and duration of visiting nature were more frequent and longer during the pandemic. As a result, people's mental health is only slightly affected because there is not an evident decrease in people's exposure to greenspace after the breakout of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Some countries did not impose strict restrictions, especially during the early time of the pandemic. For instance, a study conducted by Robinson et al (2021) found that people's greenspace use and duration of visiting nature were more frequent and longer during the pandemic. As a result, people's mental health is only slightly affected because there is not an evident decrease in people's exposure to greenspace after the breakout of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our findings, among a majority white (92%), high-income sample of residents of Vermont, participation in nature-related physical activity increased for many categories (gardening, hiking, jogging, walking, watching wildlife), and that these changes in activity engagement were associated with demographic characteristics (income, sex, employment) (Morse et al, 2020). Likewise, a survey among educated, older, primarily residents of England (96%) found that respondents significantly changed their patterns of visiting nature as a result of the COVID-19 pandemic, whereby people spent more time in nature and visited nature more often during the pandemic (Robinson et al, 2021). Similar to our findings, however, a global study with respondents from 97 countries, restrictions related to COVID-19 found reductions in naturerelated leisure activities (e.g., birding) (Randler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown increased nature-related activities in and value of nature in the US (Morse et al, 2020) and significant changes in patterns of visiting nature as a result of the COVID-19 pandemic in the UK (Robinson et al, 2021). Not only did frequency of nature-related activities change, but so did the locations, with some research reporting increased usage of nearby or neighborhood natural areas (Randler et al, 2020;Portegijs et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Planting plants in pots can also reduce the adverse effects of the Covid-19 pandemic, namely anger, anxiety, irritability, fear, irritability, and sleep disturbance (Spano et al 2021;Theodorou et al 2021). Several studies also reported that individuals had been increasingly engaging in nature activities (Ugolini et al 2020;Geng et al 2021;Robinson et al 2021). On the other hand, no study in Indonesia investigates the relationship between having more plants and mental health issues during the Covid-19 pandemic in Indonesia.…”
Section: Introductionmentioning
confidence: 99%